Kearifan Lokal di Pedesaan: Kajian Praktik Budaya Religi Di Desa Nyatnyono - adinugraha, hendri hermawan (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2018)
One element of culture in Javanese society is belief or religion. Religion has two meanings: First, religion is a religion related to God, its teachings are revealed through prophets and revelations. The truth is absolutely inviolable based on the beliefs of the adherents. Second, religion are part of culture, to fulfill collective awareness and identity. Therefore, every society has a certain way and is different from one region to another in carrying out their beliefs. Nyatnyono village, for example, they have a firm belief held in the form of a ritual carried out on certain days inherited from their ancestors. In the context of this research, religion is not only a religion but also as a cultural phenomenon as well as local wisdom which is full of values practiced by its people. Based on this explanation, this study aims to describe religious culture as a form of local wisdom in the village of Nyatnyono in Semarang Regency. This research is a descriptive qualitative type of research. The results of this study indicate that there are many religious cultures that have been adopted into local wisdom for the people of Nyatnyono Village such as the iriban tradition, merti dusun, yasinan, nyadran (ruwahan), pengajian nuzul al-Qurâ€™Än, syuronan, tirakatan, and so on. However, the tradition or habit that dominates in the village of Nyatnyono is the ziyarah of the tomb of Mbah á¸¤asan Munadi and Mbah á¸¤asan Dipuro and Mandi at Sendang Kalimah á¹¬ayyibah Â and Sendang Amanah, where it has been a hereditary culture for the Nyatnyono Village and those cultures that deliver Nyatnyono Village as one of the religious tourism icons in Semarang Regency with visitors from various regions so as to create jobs for the local community and be able to increase the Regional Revenue of Semarang Regency